Oxidation and melting characterizations of AZ91D granules during in-situ melting - Jafari, H. (Trans Tech Publications, 2011)
In this research, the oxidation and melting behaviour of AZ91D magnesium alloy granules was investigated throughout using in-situ melting technique when the granules were covered by flux. The granules were heated inside an electrical resistance furnace at four different temperatures of 650, 700, 750 and 800 °C for 30 min. Thermal analysis was used to detect the granules characteristic temperatures during the technique. The products of the heating process were examined visually and characterized by scanning electron microscopy and energy dispersive X-ray spectroscopy. The results showed that due to occurrence of severe oxidation and combustion, particularly at 800 °C, a significant amount of the granules transformed to a powdered state. The presence of the mould materials within the oxidation residue was detected indicating that severe mould-magnesium reaction occurred during heating. It was found that the granules melted during the heating process. However, the presence of oxides on the granules prevented them from fusing to form a single melt.